Precision measurements of B-meson decays at ATLAS - Biros Marek (EPJ Web of Conferences)
The precise measurement of the CP-violating phase ϕs, the average decay width Γs and the difference between the widths of the light and heavy mass eigenstates ΔΓs is presented in the Bs0$${B_s^0} $$ → J/ψϕ decay channel. Data of pp collisions at √s = 13 TeV are used, corresponding to 80.5 fb−1 of integrated lu-minosity collected by the ATLAS detector at the Large Hadron Collider in years 2015–2017. Results are statistically combined with the previous measurement with 19.2 fb−1 data with 7 and 8 TeV energy. The measured values are: ϕs = −0.087 ± 0.036 (stat.) ± 0.021 (syst.) Γs = 0.6703 ± 0.0014 (stat.) ± 0.0018 (syst.) ΔΓs = 0.0657 ± 0.0043 (stat.) ± 0.0037 (syst.). Moreover, a study estimating the ATLAS detector performance in measuring the CP-violating phase ϕs after the HL-LHC upgrade is presented.